Health symptoms and impacts of work on nursing professionals in a public hospital - Rosângela Marion da Silva; Juliana Tamiozzo; Carmem Lúcia Colomé Beck; Carolina Renz Pretto; Etiane de Oliveira Freitas; Silviamar Camponogara (SciELO, 2021)
ABSTRACT Objective: To relate self-reported health symptoms and the impacts of work in terms of physical, social, and psychological illness in nursing professionals. Method: Cross-sectional, correlational study carried out in a public hospital in the southern region of Brazil. A sample of nursing professionals who worked in direct care participated in the study. A social-occupational questionnaire of self-reported health symptoms and the Work-Related Damage Assessment Scale were used. The analysis was descriptive and analytical. Chi-square test and Spearman's correlation coefficient were used, with a significance level of 5%. Results: A total of 308 professionals participated, with a prevalence of physical illness and higher means for pain in the body, legs and back. Significant relations were identified among the social-occupational variables, health symptoms, and physical, social or psychological illness. High and moderate correlations among the factors investigated were evidenced. Conclusion: The impact of work on nursing professionals' health is evidenced by the association between self-reported health symptoms and illness, especially the physical or social one, and reinforces the need for professional awareness over situations that are harmful to health.